Chloride Ion Adsorption Enables Ampere‐Level CO2 Electroreduction over Silver Hollow Fiber. (19th September 2022) - Li, Shoujie; Dong, Xiao; Zhao, Yonghui; Mao, Jianing; Chen, Wei; Chen, Aohui; Song, Yanfang; Li, Guihua; Jiang, Zheng; Wei, Wei; Sun, Yuhan
Abstract: Electrochemical conversion of CO2 into valuable feedstocks is a promising strategy for carbon neutrality. However, it remains a challenge to possess a large current density, a high faradaic efficiency and excellent stability for practical applications of CO2 utilization. Herein, we report a facile tactic that enables exceedingly efficient CO2 electroreduction to CO by virtue of low‐coordination chloride ion (Cl − ) adsorption on a silver hollow fiber (Ag HF) electrode. A CO faradaic efficiency of 92.3 % at a current density of one ampere per square centimeter (1 A cm −2 ) in 3.0 M KCl with a sustained performance observed during a 150‐hour test was achieved, which is better than state‐of‐the‐art electrocatalysts. The electrochemical results and density functional theory (DFT) calculations suggested a low‐coordination Cl − adsorption on surface of Ag HF, which not only suppressed the competitive hydrogen evolution reaction (HER), but also facilitated the CO2 reduction kinetics. Abstract : The low‐coordination adsorbed Cl − on the surface of silver hollow fiber (Ag HF) not only suppress the competing hydrogen evolution reaction but also optimizes the kinetics of CO2 reduction to CO at ampere‐level current density.